O kilku frontyspisach XVII-wiecznych wydań dzieł Seneki - Brusewicz, Alicja (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
The article presents frontispieces of several seventeenth-century editions of Seneca’s works whose title pages draw a particular attention of a reader because they have a very interesting graphic layout. Presented are title pages of books published in Antwerp in 1605 and 1632, in Paris in 1607 and in 1627 and in Toruń in 1696. The attention was drawn to differences in a frontispieces’ composition of Antwerp’s editions which have a title in an ornamental frame, and in Paris and Toruń publications title pages have only an image of the author. The presented copies of Seneca’s works are a part of the collection of Kopernikańska Library in Toruń.
About several frontispieces of seventeenth-century editions of Senecas works
The article presents frontispieces of several seventeenth-century editions of Seneca’s works, belonging to the collection of the Kopernikańska Library in Toruń, whose title pages draw a particular attention of a reader because they have a very interesting graphic layout. Presented is a title page of published in Antwerp Seneca’s works edited by Justus Lipsius dated 1605 and their third edition dated 1632, in which – according to Lipsius’ suggestion noted in one of the copies of the first edition – an image of Seneca on the frontispiece and on early pages was changed. Seneca’s portraits were made based on drawings of Paul Rubens who sketched them according to ancient models. Carrying out of a title card and portraits in both editions was commissioned to artists from Galle studio. In 1607 in Paris published was a collective edition of works by Lucius Annaeus Seneca the Philosopher and by Annaeus Seneca the Elder or the Rhetorician with comments. This book was published again in 1627. Antwerp’s editions have a title on a title page in an ornamental frame, and in Paris publications title pages have only an image of the author. The similar situation is with the Polish translation of Seneca’s tragedies in which on the left side of the frontispiece is a philosopher’s image. This edition was published in Toruń in 1696. The title pages of seventeenth-century editions of Seneca’s works presented in this article show that these books are valuable not only for their age of four hundred years and texts of the ancient author, but also because they are evidence of a vast role of art in the history of a book.
Keywords: Seneca; Lipsius; title pages; seventeenth-century editions of Seneca’s works